2021
DOI: 10.1177/1756284821995715
|View full text |Cite
|
Sign up to set email alerts
|

Model-based effectiveness and cost-effectiveness of risk-based selection strategies for adjuvant chemotherapy in Dutch stage II colon cancer patients

Abstract: Background: We aimed to evaluate the cost-effectiveness of risk-based strategies to improve the selection of surgically treated stage II colon cancer (CC) patients for adjuvant chemotherapy. Methods: Using the ‘Personalized Adjuvant TreaTment in EaRly stage coloN cancer’ (PATTERN) model, we evaluated five selection strategies: (1) no chemotherapy, (2) Dutch guideline recommendations assuming observed adherence, (3) Dutch guideline recommendations assuming perfect adherence, (4) biomarker mutation OR pT4 stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Jongeneel et al compared several AC selection strategies in stage II cancers that were T4, and MSS tumours utilising a biomarker approach based on the presence of BRAF and KRAS mutations [ 51 ]. The study concluded that AC prescription based on molecular biomarkers (4.8%) dominates no patients receiving AC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jongeneel et al compared several AC selection strategies in stage II cancers that were T4, and MSS tumours utilising a biomarker approach based on the presence of BRAF and KRAS mutations [ 51 ]. The study concluded that AC prescription based on molecular biomarkers (4.8%) dominates no patients receiving AC.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, three of the included studies utilised such registries in modelling transitions between health states such as disease free to recurrence or death. Two studies utilised the Netherlands Cancer Registry (NCR) to develop a health model that simulates patients with stage II colon cancer from diagnosis to death [ 4 , 51 ]. The third study utilised an Australian-based multi-site colorectal cancer registry (ACCORD) to model the progression of patients following recurrence to death [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…50 Jongeneel et al compared several AC selection strategies in stage II cancers that were T4, and MSS tumours utilising a biomarker approach based on the presence of BRAF and KRAS mutations. 51 The study concluded that AC prescription based on molecular biomarkers (4.8%) dominates no patients receiving AC. Patients in this model could have received either 3-months of CAPOX or 6-months of 5FU or FOLFOX, with the biomarker strategy retaining cost-effectiveness in scenarios in which only capecitabinebased AC was prescribed.…”
Section: Oxaliplatin-based Acmentioning
confidence: 98%
“…In a recent model-based cost-effectiveness study, we showed that adding BRAF and/or KRAS mutation status as a selection criterion for adjuvant chemotherapy in stage II colon cancer can potentially improve patients' survival (9). In addition to BRAF and KRAS mutation status, the prognostic value of a large number of other molecular markers in the stage II colon cancer population has been demonstrated (5,8).…”
Section: Introductionmentioning
confidence: 99%